(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Yttrium-doped ZnO nanoparticles were synthesized by co-precipitation method to investigate structural, optical and antibacterial properties. X-ray diffraction analysis confirms hexagonal (wurtzite) structure with average crystallite size between 16 and 30 nm which is used as catalyst in synthesis of different substituted diazepine derivatives. The structures of the synthesized compounds have been confirmed on the basis of 1HNMR, IR and Mass spectral analysis.